The effect of flowering stage on distribution modelling performance: A case study of Acacia dealbata using maximum entropy modelling and RPA images - Antonio Vazquez de la Cueva; Fernando Montes Pita; Isabel Aulló-Maestro (Forest Systems, 2022)
Aim of study: To classify and validate the coverage of Acacia dealbata by stratifying its area into three different flowering stages using remotely piloted aircraft (RPA)-derived image orthomosaics.